Simplicity, Price, Quality of Service and Safety Towards The Decision to Purchase Products Through Shopee.id Application - Nursiam, N; Yanissa, Anastasia Auti Merry; Ariani, Kurnia Rina (Riset Akuntansi dan Keuangan Indonesia, 2020)
This study aims to determine the effect of simplicity, price, service quality and safety on product purchasing decisions through shopee. id application. The method used in this study is a quantitative method. Respondents in this study were accounting students for the 2016 class of the Faculty of Economics and Business, Universitas Muhammadiyah Surakarta, where the incidental sampling method was used, with a total sample of 81 respondents. Data analysis techniques used multiple linear regression models. The results of this study indicate that simplicity, price, and quality of service affect the product purchase decision through Shopee.id application with each sig value of 0,033; 0,000; and 0,000. Meanwhile, safety has no effect on product purchasing decisions through shopee.id application with a sig value of 0,087.